2005
DOI: 10.1016/j.chemgeo.2004.06.047
|View full text |Cite
|
Sign up to set email alerts
|

Determination of goslarite–bianchite equilibria by the humidity-buffer technique at 0.1 MPa

Abstract: Goslarite-bianchite equilibria were determined along four humidity-buffer curves at 0.1 MPa and between 27 and 36 8C. Results, based on tight reversals along each humidity buffer, can be represented by ln K (F0.005)=19.643À7015.38/T, where K is the equilibrium constant and T is temperature in K. Our data are in excellent agreement with several previous vapor-pressure measurements and are consistent with the solubility data reported in the literature. Thermodynamic analysis of these data yields 9.634 (F0.056) k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…However, Hemingway et al [2002] found that the thermodynamic properties of hydrated sulfate minerals, including enthalpy and Gibbs free energy of formation and entropy, can be accurately estimated on the basis of the summation of known properties of component phases (). Subsequent experimental studies have confirmed the accuracy of these estimation methods [ Chou et al , 2002; Chou and Seal , 2003, 2005]. Thus the location of the MgSO 4 ·11H 2 O‐epsomite stability boundary as a function of temperature and RH can be accurately estimated (Figure 6).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…However, Hemingway et al [2002] found that the thermodynamic properties of hydrated sulfate minerals, including enthalpy and Gibbs free energy of formation and entropy, can be accurately estimated on the basis of the summation of known properties of component phases (). Subsequent experimental studies have confirmed the accuracy of these estimation methods [ Chou et al , 2002; Chou and Seal , 2003, 2005]. Thus the location of the MgSO 4 ·11H 2 O‐epsomite stability boundary as a function of temperature and RH can be accurately estimated (Figure 6).…”
Section: Discussionmentioning
confidence: 75%
“…This paper investigates hydration and dehydration equilibria under liquid‐absent conditions between hexahydrite and starkeyite (MgSO 4 ·4H 2 O) and uses these results with previously published results on the hydration and dehydration equilibria between epsomite and hexahydrite to understand better the phase relations in the system MgSO 4 ‐H 2 O; the humidity buffer technique used in these studies has proven to be superior in precision to other currently available techniques for investigating experimental reversals for hydration and dehydration reactions at low temperatures [ Chou et al , 2002; Chou and Seal , 2003, 2005]. These results are used to evaluate stable and metastable equilibria and then these reactions are extrapolated rigorously using thermodynamic principles to conditions found on Mars.…”
Section: Introductionmentioning
confidence: 99%
“…There has been some confusion in the literature as to whether starkeyite is a stable phase (e.g., Archibald and Gale, 1924;Balarew et al, 2001) but reactions between starkeyite and hexahydrite have been reversed Chou et al, 2005) suggesting that there is a definite thermodynamic stability field for starkeyite. Balarew et al (2001) conducted an interesting study where they precipitated Mg-sulfate hydrates from various solutions of MgCl 2 -MgSO 4 .…”
Section: General Stabilitymentioning
confidence: 99%
“…The shaded field represents the general range of temperature and relative humidity conditions in the eastern United States during the summer. Data sources for curves are: (1) melanterite and rozenite (dotted lines); chalcanthite and bonattite (solid line) (Chou et al, 2002), (2) epsomite, hexahydrite, and kieserite (Chou and Seal, 2003a), (3) morenosite and retgersite (dash-dot line) (Chou and Seal, 2003b), (4) bieberite and moorhouseite (heavy line) (Chou and Seal, 2003c), and (5) goslarite, bianchite, and gunningite (dashed lines) (Chou and Seal, this volume). laboratory, crystallized to copiapite. Blue salts that formed on flotation tailings at the Ely mine are melanterite that incorporates solid solution Cu and Co (Hammarstrom et al, 2001b).…”
Section: Mineralogymentioning
confidence: 99%